Fierce invalids home from hot climates - Robbins, Tom, 1932- (Bantam Books, 2003)
The bestselling author of "Half Asleep in Frog Pajamas" and "Skinny Legs and All" makes his triumphant return. Robbins explores, challenges, mocks, and celebrates virtually every major aspect of our contemporary era as he brings onstage the most complex and compelling character he's ever created.